Analisis Perubahan Arsitektural Masjid Agung Kota Tegal - Mohamad Zuhdan Fanani Abdullah; Sahrul Aditia Putra (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The Great Mosque of Tegal City is a historic building that has undergone numerous renovations since its establishment in 1825-1830. These renovations aimed not only to meet the functional and capacity needs of worshippers but also reflected modern architectural trends, occasionally compromising historical elements. This study employs a qualitative approach using documentation, observation, and literature synthesis methods to analyze the mosque's architectural changes. Using John Obert Voll's